Insights Into Mechanisms of Biofilm Formation in Acinetobacter baumannii and Implications for Uropathogenesis - Colquhoun, Jennifer M.; Rather, Philip N. (Frontiers in Cellular and Infection Microbiology, 2020)
Multidrug resistant Acinetobacter baumannii is a serious healthcare threat. In fact, the Center for Disease Control recently reported that carbapenem-resistant A. baumannii is responsible for more than 8,500 infections, 700 deaths, and 281 million in healthcare costs annually in the United States with few, if any, treatment options available, leading to its designation as a pathogen of urgent concern and a priority for novel antimicrobial development. It is hypothesized that biofilms are, at least in part, responsible for the high prevalence of A. baumannii nosocomial and recurrent infections because they frequently contaminate hospital surfaces and patient indwelling devices; therefore, there has been a recent push for mechanistic understanding of biofilm formation, maturation and dispersal. However, most research has focused on A. baumannii pneumonia and bloodstream infections, despite a recent retrospective study showing that 17.1% of A. baumannii isolates compiled from clinical studies over the last two decades were obtained from urinary samples. This highlights that A. baumannii is an underappreciated uropathogen. The following minireview will examine our current understanding of A. baumannii biofilm formation and how this influences urinary tract colonization and pathogenesis.